Father Involvement in Complementary Feeding and Growth Follow-Up to Avoid Stunting in Rural Brebes, Indonesia: A Qualitative Study - Taufik Maryusman; Suhartono; Sri Achadi Nugraheni; Apoina Kartini (Media Gizi Indonesia, 2026)
There is little literature on fathers’ roles in complementary feeding and monitoring children’s growth in rural areas aged 6-23 months. This study aimed to understand the role of fathers in complementary feeding behaviors and growth-monitoring behaviors, such as household nutrition decision-making and attendance at primary health services in rural Brebes, Central Java, Indonesia. We conducted a qualitative study using direct observation, focus group discussions, and document review with fathers of children at risk of stunting and key stakeholders (community leaders, heads of community health centers, nutrition workers, and district health officials). Thematic analysis of the data was conducted to identify patterns in caregiving and decision-making. Fathers determined household food distribution and health-seeking behavior, helped with access to social support systems, and influenced parenting behavior in terms of stimulation and caregiving. Active involvement of fathers increased family communication and compliance with recommended nutrition and health practices, whereas community-based programs that aligned with community sociocultural standards increased participation and acceptability. In summary, primary health care and community-based strategies to combat stunting, aimed at enhancing complementary feeding and growth monitoring practices, must prioritize father-targeted strategies.